The green lacewing genus Kuwayamachrysa Tsukaguchi & Tago, 2018 from China, with description of two new species based on morphological and molecular evidence - Wang, Maozhi; Lai, Yan; Liu, Xingyue (Zootaxa, 2025)
Previously, Kuwayamachrysa Tsukaguchi & Tago, 2018 (Neuroptera: Chrysopidae: Chrysopinae) was known as a monotypic green lacewing genus from the Palearctic region. Here we described two new species of Kuwayamachrysa from China: Kuwayamachrysa wujiaoensis sp. nov. and Kuwayamachrysa neptuna sp. nov. Also, Mallada qinlingensis Yang, 1989, currently named as Apertochrysa qinlingensis (Yang, 1989), is recognized as a junior synonym of Kuwayamachrysa kichijoi (Kuwayama, 1936). A key to the Kuwayamachrysa species is provided. The standard DNA barcoding region of cytochrome c oxidase subunit I (COI) of these species was sequenced for the verification of the new species.